Mobilization of Fiscal Resources as Development Engine of Decentralized Territorial Entities: The case study of Mbandaka City in Democratic Republic of the Congo - Jacqueline Kangu Kobe; Placide Makwa Mbulola; Gédéon Ngiala Bongo; Ruphin Djolu Djoza; Muhammad Ridwan; Koto-Te-Nyiwa Ngbolua (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The State as an institution was born from the will of the people for the realization of activities of common interest, such as: the building of hospitals, roads, schools, electrification, job creation, water etc. As the protector of goods, the state is called upon to fulfill several duties either governmental, when the state exercises its sovereignty to legislate and execute, or administrative when it ensures the management of the public administration for the benefit of the collective welfare thanks to the various taxes, levies and other charges mobilized and/or collected from the population in order to meet its expectations and aspirations. The modern State fulfills five important socio-economic duties, which are: production, regulation, protection, compensation and finally the function of stabilization and stimulation of the economic growth. Through production, the state intervenes not only to produce and create material wealth, but also to ensure the necessary conditions for its creation (e.g., provide adequate infrastructure and create an efficient administration). The state plays the role of the father of the city, must demonstrate certain equity through distributive justice, ensuring the redistribution of income by means of taxation on the income of the individual and the profit of the corporations or by means of aid and social security. Finally, the state has the responsibility of stabilizing and stimulating the economic growth. To achieve this, it is vital to practice the policy of full employment, price stability and very rapid economic growth, with the aim of increasing the quantity, quality and mobility of production factors, it is reflected in the policy of education, scientific research and training as well as labor mobility. Thus, local elected officials are called upon to fulfill these different functions in order to take off the development of their areas of common interest for the benefit of community welfare at the grassroots level.